Analysis of Language Errors in News Texts in the April 2023 Edition of Derap Guru Magazine as the Feasibility of Reading Teaching Materials for Grade VIII Junior High School Students - Dhenok Aurorra Candra Pradwipta; Widyadhana Benda S.Nismara; Dea Nisa Febrianti; Sabrina Fadilatul Khoiroh; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Qurrota Ayu Neina; Riyadi Widhiyanto (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2024)
The accuracy of language in news texts is critical because appropriate language makes it easier for readers to understand. The quality of correct and appropriate language is essential in conveying information that is clear, accurate, and easy for readers to understand. Language errors in news texts can interfere with understanding and affect readers' minds. Therefore, correcting language errors in news texts, especially for junior high school students, is essential as part of the learning process. This research aims to provide a deeper understanding of language errors in the news texts studied, using data collection methods, listening and note-taking techniques, and analysis using the agih method. The research used a qualitative descriptive design approach to analyze errors in language use in news texts in the April 2023 Edition of Derap Guru Magazine, which included errors in conjunctions, punctuation, spelling, standard words, capital letters, abbreviated words, and ineffective sentences. Students can improve their language skills by analyzing language usage errors in news texts as teaching materials while deepening their understanding of news texts and effective language use.